C-reactive protein-albumin-lymphocyte (CALLY) index predicts overall survival in elderly Japanese patients with dysphagia: a retrospective cohort study - Pan, Wenxiu; Yang, Yawen; Song, Xiaohui; Wang, Jixian; Xie, Qing (Frontiers in Nutrition, 2025)
BackgroundThe C-reactive protein-albumin-lymphocyte (CALLY) index serves as an established prognostic biomarker across multiple severe disease cohorts. Nevertheless, limited research has examined its relationship with overall survival among elderly Japanese individuals experiencing dysphagia.ObjectiveTo evaluate the prognostic utility of the CALLY index for overall survival in a cohort of elderly Japanese patients with dysphagia.MethodsWe conducted a retrospective single-center cohort study of 248 patients diagnosed with dysphagia between January 2014 and January 2017. The primary outcome was overall survival. The CALLY index was analyzed both continuously (natural log transformation) and by quartiles. Multivariable Cox proportional hazards models adjusted for relevant demographic, clinical, and nutritional covariates (including age, sex, comorbidities, hemoglobin, feeding modality, and daily caloric intake) were used to estimate hazard ratios (HR) and 95% confidence intervals (CI). Restricted cubic spline models assessed dose–response relationships. Kaplan–Meier analysis estimated median survival by CALLY quartile; subgroup analyses examined effect modification.ResultsAfter natural log transformation, the CALLY index was independently associated with improved survival (HR = 0.85, 95%CI: 0.76–0.95, p = 0.003). Using the lowest quartile (Q1) as reference, adjusted HR were 0.73 (95%CI: 0.46–1.16, p = 0.179) for Q2, 0.56 (95%CI: 0.34–0.90, p = 0.018) for Q3, and 0.44 (95%CI: 0.25–0.78, p = 0.005) for Q4. Restricted cubic spline analysis indicated a positive, approximately linear relationship between the CALLY index and overall survival. Median survival times were 887, 785, 362, and 153 days for Q4, Q3, Q2, and Q1, respectively. Subgroup analyses showed no significant interactions across prespecified strata.ConclusionIn this cohort of elderly Japanese patients with dysphagia, a higher CALLY index was associated with longer overall survival. These findings support the potential prognostic utility of the CALLY index in this population; prospective and multicentre validation is warranted.